Identification of Prognostic Factors in Patients With Streptococcus Bloodstream Infection - Duan, Xiaoguang; Zhang, Ruifang; Zhang, Xiaojuan; Ding, Xianfei; Sun, Tongwen (Frontiers in Medicine, 2022)
Aim: The purpose of this study was to explore prognostic factors of bloodstream infections (BSIs), a common severe infection and a major cause of mortality worldwide, so as to construct a prognosis model of patients with BSI. Materials and methods: Clinical and biochemical test data were obtained retrospectively from the medical records of 562 patients with BSI who had been treated at a single center; the end point was 60 days of all-cause death. The chi-square test was used to compare the mortality of patients grouped by the types of antibiotic treatment. The logistic regression analysis was adopted to identify prognostic factors; the Kaplan–Meier survival curve and log-rank test were conducted to compare the survival rate of patients with different prognostic factors; the receiver operating characteristic (ROC) curve was used to estimate the predictive value of different prognostic factors. Results: Of the 562 patients, 455 survived (80.96%), and 107 died (19.04%). The mortality rate of patients treated with a combination of antibiotics (25.40%) was higher than that treated with a single antibiotic (15.82%). Univariate analysis identified 19 prognostic factors for patients with BSI, including gender, age, diabetes, malignant tumor (non-blood system), total hospitalization time, alanine aminotransferase, aspartate aminotransferase, total protein, albumin, total bilirubin, direct bilirubin, creatinine, ratio of granulocytes, fibrinogen, D-dimer, platelet, C-reactive protein, shock, and respiratory failure (P < 0.05). Multivariate analysis indicated that albumin (odds ratio [OR] = 0.94, 95% confidence interval [CI]: 0.89–0.99), fibrinogen (OR = 0.61, 95%CI: 0.46–0.82), shock (OR = 16.61, 95%CI: 7.00–39.41), and respiratory failure (OR = 47.53, 95%CI: 19.93–133.64) were independent factors. The combination of four indicators demonstrated a favorable predictive value for the 60-day outcome of patients with BSI, with an area under the ROC of 0.96 (95%CI: 0.94–0.99), sensitivity of 90.65%, specificity of 94.95%, and accuracy of 94.13%. Conclusions: Shock, respiratory failure, albumin, and fibrinogen are potential independent prognostic factors for 60-day mortality.